How Rory Thorne destroyed the multiverse - Eason, K. (Eason, K. Thorne chronicles, 2019)
Princess Rory Thorne must use the fairy blessings gifted to her at birth to change the multiverse--or possibly destroy it. How Rory Thorne Destroyed the Multiverse is a feminist reimagining of familiar fairytale tropes and a story of resistance and self-determination--how small acts of rebellion can lead a princess to not just save herself, but change the course of history.